Aliphatic Hydrocarbons In Surface Sediments From South China Sea Off Kuching Division, Sarawak - Yusoff, Abdul Hafidz; Assim, Zaini; Mohamad, Samsur (International Atomic Energy Agency, 2012)
Eighteen surface sediment samples collected from South China Sea off Kuching Division, Sarawak were analyzed for aliphatic hydrocarbons. These hydrocarbons were recovered from sediment by Soxhlet extraction method and then analyzed using gas chromatography equipped with mass spectrometer (GC/MS). Total concentrations of aliphatic hydrocarbons in surface sediments from South China Sea off Kuching division are ranged from 35.6 ug/g to 1466.1 ug/g dry weights. The sediments collected from Bako Bay, Kuching showed high concentrations of total aliphatic hydrocarbons. Several molecular indices were used to predict the predominant sources of hydrocarbons. Carbon preference index (CPI) value revealed widespread anthropogenic input in this study area (CPI= 0 to 4.1). The ratio of C31/C19and C29/C31indicated that major input of aliphatic hydrocarbon mostly transfer by lateral input to the marine environment than atmospheric movements. Generally, the concentrations of aliphatic hydrocarbons in sediment from South China Sea off Kuching division are generally higher compare to other area in the world.